1974
DOI: 10.1088/0022-3719/7/17/024
|View full text |Cite
|
Sign up to set email alerts
|

Grain-size effects on properties of some ferroelectric ceramics

Abstract: Hot-pressed ceramics of the lead titanate zirconate system with different grain sizes were prepared and some of their electrical properties measured. The values of the dielectric and piezoelectric properties were analysed together with information on barium titanate ceramics already published in the literature. Many similarities were found between both systems. There are two main contributions to the properties : the single-crystal single-domain intrinsic effect and the contribution of the wall motion. These t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
133
1
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(161 citation statements)
references
References 20 publications
13
133
1
1
Order By: Relevance
“…The substitution of W 6+ for Ta 5+ in SBT results in the formation of cation vacancies which effectively reduces the concentration of oxygen vacancies which in turn significantly reduce the dielectric loss. Reduction in loss have been reported in other donor doped BLSFs also [25,49]. Fig.…”
Section: Dielectric Studiessupporting
confidence: 62%
See 2 more Smart Citations
“…The substitution of W 6+ for Ta 5+ in SBT results in the formation of cation vacancies which effectively reduces the concentration of oxygen vacancies which in turn significantly reduce the dielectric loss. Reduction in loss have been reported in other donor doped BLSFs also [25,49]. Fig.…”
Section: Dielectric Studiessupporting
confidence: 62%
“…This decrease in conductivity upon donor substitution improves the poling efficiency and thus higher d 33 values are obtained. It has also been reported that the incorporation of higher valent ions accompanied with cation vacancies at the A site in BLSFs, improves not only the ferroelectric property but also the piezoelectric one [49,125]. The piezoelectric constants have also been found to increase with increase in grain size [49].…”
Section: Piezoelectric Studiesmentioning
confidence: 90%
See 1 more Smart Citation
“…A diffuse phase transition is produced due to an inhomogeneous tension distribution originated by a reduced grain area. 25 It varies slightly the temperature of the maximum of permittivity from one grain to another. The observed anomaly at the transition would be the convolution of the different transition anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] This dependence demonstrates an increase [13][14][15][16] as well as a decrease 17,18 of dielectric constant with decreasing the grain size.…”
Section: Introductionmentioning
confidence: 99%